Epidemiological, hematological and biochemical profile in dogs with Dirofilaria sp. in Ceara (Research, Society and Development, 2021)
Heartworm disease is an important zoonosis considered to be endemic in Brazil, whose transmission occurs mainly through mosquito vectors of the genera Culex, Aedes and Anopheles and which have the domestic dog as its host. Although most animals are asymptomatic, the disease can affect several organs, culminating in possible changes in laboratory diagnoses. Different diagnoses can be used, being the visualization of microfilariae of Dirofilaria spp. in blood smear the most used. The objective of this work was to verify the hematological and biochemical profile of dogs diagnosed with Dirofilaria immitis microfilariae in the city of Fortaleza, Ceará. Blood samples were selected from August 2014 to June 2018. In samples where there was positivity for the presence of microfilariae in the blood smear, a survey of the changes found in hematological and biochemical tests was carried out. In 2,400 blood samples analyzed, 26 had microfilariae (1.1%), with 46% of anemia and 46% with signs of erythrocyte regeneration, 42% had thrombocytopenia and 46% hyperproteinemia, with lymphopenia in 61% of cases. In the biochemical profile, slight alterations below normal were observed, except for albumin, which was reduced in 62% of cases. Most analytes had normal values, indicating that there was no organ hyperfunction or hyperactivity. Therefore, heartworm disease influenced canine immunology and probably induced a reduction in the number of platelets and an increase in total proteins by the inflammatory stimulus generated.